PENGARUH KEMISKINAN, PDRB, DAN ANGGARAN KESEHATAN TERHADAP PREVALENSI STUNTING DI KABUPATEN/KOTA PROVINSI NUSA TENGGARA - Maromi M. Mbate; Jemmy J. S. Dethan; Melvin K. Djami Rane (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2026)
Stunting remains an important public health problem in Indonesia, including in East Nusa Tenggara Province, which records a higher prevalence than the national average. This study aims to analyze the effects of poverty, Gross Regional Domestic Product (GRDP), and health expenditure on stunting prevalence in 22 regencies/cities in East Nusa Tenggara Province during 2020–2024. The study uses secondary panel data obtained from official government publications. Data were analyzed using panel regression, and the best-fitting model was the Fixed Effect Model. The results show that poverty has a positive and significant effect on stunting, while GRDP and health expenditure have negative and significant effects on stunting. Simultaneously, the three variables significantly affect stunting prevalence. These findings confirm that stunting is a multidimensional problem that requires cross-sector policies through poverty reduction, regional economic strengthening, and increased health spending.